Основні принципи математичного моделювання динаміки транспортування рідкого вантажу та дослідження на параметричний резонанс в умовах перерозподілу мас в цистерні - Кожушко, Андрій Павлович; Григор'єв, Олександр Львович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Моделюється процес транспортування рідкого вантажу в баку або цистерні при наявності поверхні розділу між рідиною і газом. Коливання стінок призводять до перетікання вздовж вільної поверхні і перерозподілу маси рідини в цистерні. Показано, що при несприятливих умовах пов'язані вертикальні і горизонтальні коливання рідини призводять до виникнення параметричного резонансу. Формулюються принципи і призначаються етапи розробки нової математичної моделі, здатної досліджувати процес транспортування рідкого вантажу з урахуванням основних лінійних і нелінійних зв'язків між параметрами руху, а також можливістю появи резонансів. При описі коливань рідини використовується дискретна модель парціальних осциляторів, в яку внесено ряд допустимих спрощень. Прийняті принципи використані для дослідження поздовжніх і поперечних коливань трактора, який на причепі перевозить цистерну з рідиною. Виконано розрахункове дослідження зміни параметрів руху транспортного засобу в околиці параметричного резонансу.

The process of transportation of a liquid cargo in a tank or cistern is simulated in the presence of an interface between liquid and gas. Oscillations of the walls lead to overflow along the free surface and redistribution of the mass of liquid in the tank. It is shown that, under unfavorable conditions, coupled vertical and horizontal oscillations of the liquid lead to the appearance of parametric resonance. Principles are formulated and stages are assigned for the development of a new mathematical model capable of investigating the process of transporting a liquid cargo, taking into account the main linear and nonlinear relationships between the motion parameters, as well as the possibility of resonances. When describing fluid oscillations, a discrete model of partial oscillators is used, into which a number of permissible simplifications have been introduced. The outlined simplifications are based on the principle of equivalent replacement of the real shape of the container with the shape of a rectangular parallelepiped. The principle of reduction is to preserve the size of the free surface of the liquid and the mass of the liquid in the tank. It is established that for problems with ergonomic criteria, it is enough to use three partial oscillators for each form of oscillations: longitudinal, transverse and torsional. The principles adopted were used to study the longitudinal and lateral vibrations of a tractor that transports a tank with a liquid on a trailer. A computational study of the change in the parameters of the vehicle movement in the vicinity of the parametric resonance is carried out. During the simulation it is shown that the parametric resonance is significantly influenced by the properties of the transported fluid and the characteristics of the external kinematic excitation.
Basic principles of mathematical modeling dynamics transportation liquid cargo and research on parametric resonance under conditions of oil redistribution in a tank
Keywords: колісний трактор; коливання; wheeled tractor; oscillations